Identificación y análisis de los criterios de cambios del sistema de distribución turístico asociados al uso intensivo de las tecnologías de la información y de la comunicación - Carmen Berné Manero; Margarita García-González; M. Esperanza García-Uceda; José Miguel Múgica Grijalba (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2013)
– There is unanimous acknowledgement in the literature in that information and communication technologies (ICT) can improve the effectiveness of cooperation between tour operators and help in the development of the tourism industry. However, there is no empirical research that supports the reduced uncertainty about the future structure of the sector resulting from the changes induced by ICT. The objective of this paper is to attempt to fill this gap, firstly by identifying the change criteria found in the research literature, and secondly, to apply the resulting theoretical framework using the data collected in a survey of tourism intermediaries.
Keywords: D30; L83; O30; 330; Distribution channels; Distribution system